Patient-derived cornea organoid model to study metabolomic characterization of rare disease: aniridia-associated keratopathy - Ali Can Koc; Vedat Sari; Gamze Kocak; Tuba Recber; Emirhan Nemutlu; Daniel Aberdam; Sinan Güven (BMC Ophthalmology)
Abstract Background Aniridia is a rare panocular disease caused by gene mutation in the PAX6, which is essential for eye development. Aniridia is inherited in an autosomal dominant manner, but its phenotype can vary significantly among individuals with the same mutation. Animal models, such as drosophila, zebrafish, and rodents, have been used to study aniridia through Pax6 deletions. Recently, patient-derived limbal epithelial stem cells (LESCs) and human-induced pluripotent stem cells (hiPSCs) have been used to model the disease in vitro, providing new insights into therapeutic strategies. Methods In this study, corneal organoids were generated from hiPSCs derived from aniridia patients with three different PAX6 nonsense mutations, allowing for a detailed comparison between diseased and healthy control models. These organoids structurally mimicked the human cornea and were used to investigate histologic and metabolomic differences between healthy and aniridia-derived samples. Results Untargeted metabolomic analysis revealed significant metabolic differences between wild-type (WT) and aniridia-associated keratopathy (AAK) hiPSCs. Further metabolomic profiling at different time points demonstrated distinct metabolic shifts, with amino acid metabolism pathways being consistently enriched in AAK organoids. Conclusions This study emphasizes the profound impact of AAK mutations on metabolism, particularly in amino acid biosynthesis and energy metabolism pathways.